Recent advances in therapeutic strategies for Alzheimer's and Parkinson's disease using protein/peptide co‐modified polymer nanoparticles - Ramesha Hanumanthappa; Aravind Parthasarathy; Geetha B. Heggannavar; Kiran PC; Hemalatha Nanjaiah; Ramhari Kumbhar; Kuramkote Shivanna Devaraju (Neuroprotection)
Abstract The blood‐brain barrier (BBB), which protects the brain from foreign molecules, makes delivery of drugs to the central nervous system is challenging. Nanoparticles (NPs) have been used over the past decade as drug delivery systems for the treatment of many disorders with great results. However, the effectiveness of NPs in delivering drugs to the brain for the treatment of Alzheimer's disease (AD) and Parkinson's disease (PD) is limited by the BBB. A recent breakthrough in nanotechnology delivery systems involves the use of surface‐modified polymer NPs that enhance drug absorption and transport across the BBB; however, the technology still has some limitations. Studies conducted over the past few years have demonstrated that NPs modified with peptides or proteins can effectively cross the BBB via specific receptors, thus enhancing their delivery efficiency. In this review, we explore the use of polymer NPs combined with peptides and proteins for the treatment of AD and PD. This discussion focuses on the pathophysiology of these diseases, the BBB, and the potential of therapeutics based on co‐modifying NPs with peptides and proteins. Additionally, we outline future directions for the use of polymer NPs conjugated with these biomolecules.